Discovery of VU0431316: A negative allosteric modulator of mGlu(5) with activity in a mouse model of anxiety - Bates, Brittney S. (2014)
Development of SAR in an aryl ether series of mGlu(5) NAMs leading to the identification of pyrazine analog VU0431316 is described in this Letter. VU0431316 is a potent and selective non-competitive antagonist of mGlu(5) that binds at a known allosteric binding site. VU0431316 demonstrates an attractive DMPK profile, including moderate clearance and good bioavailability in rats. Intraperitoneal (IP) dosing of VU0431316 in a mouse marble burying model of anxiety, an assay known to be sensitive to mGlu(5) antagonists and other anxiolytics, produced dose proportional effects.